2023
DOI: 10.7554/elife.82626
|View full text |Cite
|
Sign up to set email alerts
|

Targeted multi-omic analysis of human skin tissue identifies alterations of conventional and unconventional T cells associated with burn injury

Abstract: Burn injuries are a leading cause of unintentional injury, associated with a dysfunctional immune response and an increased risk of infections. Despite this, little is known about the role of T cells in human burn injury. In this study, we compared the activation and function of conventional T cells and unconventional T cell subsets in skin tissue from acute burn (within 7 days from initial injury), late phase burn (beyond 7 days from initial injury), and non-burn patients. We compared T cell functionality by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…121 In burn injury, skin T-cell populations shift from a resident phenotype to a circulating homing marker profile. 122 In later stages of epithelial injury, skin-resident γδ-T cells and BATF + CCR8 + skin T regs are thought to promote physiological wound healing by partaking in a tightly regulated response comprising pro-/anti-inflammatory signals and growth factors, 123,124 whereas increased numbers of TNFα-producing CD8 + memory T cells were found in hypertrophic (keloid) scars. 125 As first line of defense, T RM are considered important targets in vaccine design, 126 and the route of vaccine administration will be critical to promote the generation of protective CD8 + T RM in barrier tissues.…”
Section: Barrier Defense Wound Healing and Protection Against Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…121 In burn injury, skin T-cell populations shift from a resident phenotype to a circulating homing marker profile. 122 In later stages of epithelial injury, skin-resident γδ-T cells and BATF + CCR8 + skin T regs are thought to promote physiological wound healing by partaking in a tightly regulated response comprising pro-/anti-inflammatory signals and growth factors, 123,124 whereas increased numbers of TNFα-producing CD8 + memory T cells were found in hypertrophic (keloid) scars. 125 As first line of defense, T RM are considered important targets in vaccine design, 126 and the route of vaccine administration will be critical to promote the generation of protective CD8 + T RM in barrier tissues.…”
Section: Barrier Defense Wound Healing and Protection Against Infectionmentioning
confidence: 99%
“…In clearance of infection and in wound healing, tissue‐resident T regs come into action: Directly following barrier breach, skin‐resident T regs initially promote inflammation at the keratinocyte layer 121 . In burn injury, skin T‐cell populations shift from a resident phenotype to a circulating homing marker profile 122 . In later stages of epithelial injury, skin‐resident γδ‐T cells and BATF + CCR8 + skin T regs are thought to promote physiological wound healing by partaking in a tightly regulated response comprising pro‐/anti‐inflammatory signals and growth factors, 123,124 whereas increased numbers of TNF‐α‐producing CD8 + memory T cells were found in hypertrophic (keloid) scars 125 …”
Section: Functions Of Skin Trmmentioning
confidence: 99%
“…However, another study on the role of CD4 + and CD8 + T-cells in mouse skin wound healing found that the absence of either CD4 or CD8 lymphocytes changes infiltration of inflammatory cells and profiles of cytokine expression, but does not impair healing ( Chen et al, 2014 ). In response to burn injuries, Labuz et al (2023) found that conventional CD3 + T cells and MAIT cells produce elevated levels of critical pro-inflammatory cytokines than in non-burn tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] However, given the discrepancy in the proportion of different immune cells residing in mouse and human skin tissues, the role of human unconventional T cells in tissue repair is not well understood. 15,16 Using targeted multi-omic analyses, Labuz et al 17 characterized the landscape of conventional and unconventional T cell subsets associated with human burn injuries. They first used flow cytometry to address the frequency and phenotype of different T cell subsets in burnt vs non-burnt human tissue samples.…”
mentioning
confidence: 99%